Review of biological and engineering aspects of algae to fuels approach - Chen, Paul; Min, Min; Chen, YiFeng; Wang, Liang; Li, Yecong; Chen, Qin; Wang, Chengguang; Wan, Yiqin; Wang, Xiaoquan; Cheng, Yanling; Deng, Shaobo; Hennessy, Kevin; et al. (International Journal of Agricultural and Biological Engineering, 2010)
Current biofuel production relies on limited arable lands on the earth, and is impossible to meet the biofuel demands. Oil producing algae are alternative biofuel feedstock with potential to meet the world's ambitious goal to replace fossil fuels. This review provides an overview of the biological and engineering aspects in the production and processing technologies and recent advances in research and development in the algae to fuels approach. The article covers biology, selection and genetic modification of algae species and strains, production systems design, culture media and light management, harvest and dewatering, downstream processing, and environment and economic assessment. Despite the many advances made over several decades, commercialization of algal fuels remains challenging chiefly because of the techno-economic constraints. Technological breakthroughs in all major aspects must take place before commercial production of algal fuels becomes economically viable. Keywords: algae, microalgae, open pond, enclosed photobioreactor, light, harvest, dewatering, extraction, hydrothermal liquefaction, gasification, pyrolysis, fermentation DOI: 10.3965/j.issn.1934-6344.2009.04.001-030 Citation: Paul Chen, Min Min, Yifeng Chen, Liang Wang, Yecong Li, Qin Chen, et al. Review of the biological and engineering aspects of algae to fuels approach. Int J Agric & Biol Eng, 2009; 2(4): 1